Monitoring DNA Provirus Virus Penyakit Jembrana Pada Sapi Bali Dengan Metode PCR - Krisnayanti, Ni Putu Eka; Pharmawati, Made; Narayani, Inna; Agustini, Ni Luh Putu (Metamorfosa: Journal of Biological Sciences, 2020)
The development of biotechnology in molecular field make it possible to detect the presence of a disease earlier, faster and more accurately. One of the technique in biotechnology which has been highly developed and often be used in biological and medical research is PCR method. This molecular technique allows to accurately identify the DNA level in presence of a particular disease. This study aims to do monitoring the presence of proviral DNA Jembrana Disease Virus in bali cattle from all regencies in Bali. The blood samples of bali cattle is taken from all regencies in Bali in 2017 as many 170 samples and in 2018 from Buleleng Regency there are 101 samples and form Karangasem Regency 152 samples. DNA is extracted by QIAamp DNA blood mini kit and samples from 2017 is made to 34 pool samples, whereas samples from 2018 is made to 20 pool samples (Buleleng Regency) and 30 pool samples (Karangasem Regency). PCR is conducted by JDV 1 primer and JDV 3 primer in total reaction 25 µL with 35 cycles. PCR is also conducted on positive control and negative control. The result indicate that 34 pool samples of bali cattle from 2017 or 20 pool samples and 30 pool samples from 2018 is not indicate the presence of proviral DNA Jembrana Disease Virus. Keyword : PCR, proviral DNA, Jembrana Disease Virus